101 Foods That Could Save Your Life - Grotto, David W. (London Bantam Books, 2010)
When it comes to food, nature provides a wealth of delicious choices. But each one also supplies unique health benefits. This guide presents 101 power foods. It also includes a history of the food's origin, therapeutic benefits along with scientific research, tips for use and preparation, and an appetizing recipe
Include Reference and Index
Keywords: Natural foods -- Diet therapy -- Nutrition